Encyclopedia of survey research methods - Lavrakas, Paul J. (SAGE Publications, 2008)
In conjunction with top survey researchers around the world and with Nielsen Media Research serving as the corporate sponsor, the Encyclopedia of Survey Research Methods presents state-of-the-art information and methodological examples from the field of survey research.